Estafette of resonances, stochasticity and control of particle motion - Shishkin, A.A. (Вопросы атомной науки и техники, 2000)
A new method of particle motion control in toroidal magnetic traps with rotational transform using the estafette of drift resonances and stochasticity of particle trajectories is proposed. The using the word "estafette" (relay race) means here that the particle passes through a set of resonances consistently from one to another during its motion. The overlapping of adjacent resonances can be moved radially from the center to the edge of the plasma by switching on the corresponding perturbations in accordance with a particular rule in time. In this way particles (e.g. cold alpha-particle) can be removed from the center of the confinement volume to the plasma periphery.